The DMCA's Anti-Device Provisions: Impeding the Progress of the Useful Arts? - Craig Allen Nard (Washington University Journal of Law & Policy, 2002)
In 1998, the U.S. Congress enacted the Digital Millennium Copyright Act (DMCA). The DMCA extensively revised the U.S. copyright law in a manner not seen since the Copyright Act of 1976. Commentators have written a great deal about the DMCA, particularly its broad anti-circumvention provisions, embodied in 17 U.S.C. § 1201. Much of the commentary on these provisions is critical, largely because these provisions have the effect, with some important exceptions, of greatly limiting access to and usage of works protected by “technological measures.” This effect occurs regardless of whether these works are in the public domain or subject to copyright protection. In fact, the anti-circumvention provisions aim to prevent activity far beyond that which would constitute copyright infringement. This Essay raises two points about the anti-circumvention provisions. First, these provisions seem inconsistent with the culture of intellectual property. In the world of proprietary boundaries and public domains, there is something special about access to protected works and the use of limits to avoid infringement, whether we are talking about fairly using copyrighted works or designing-around patented technology. Indeed, cultural enrichment and technological advancement are achieved by fairly using artistic expression and building upon technical knowledge. The focus of this Essay is on the access and use of artistic expression in patent law. Second, the anti-circumvention provisions of the DMCA, which aim to protect digital expression by erecting technological fences, have both an expressive and a technical component. These provisions are meant to prevent unauthorized access to and usage of expressive content by prohibiting: (1) access per se to works protected by technological measures, and (2) the manufacture and trafficking of devices primarily designed to circumvent technological restrictions. Thus, patent law, as well as copyright law, addressed this issue of circumvention-enabling technology. Circumvention-enabling technology, such as software, comprises patentable subject matter, and, resultantly, raises questions about the effect of the anti-circumvention provisions on patent law’s constitutional mission to promote the progress of the useful arts. In particular, assuming patent protection is important to the manufacturers of circumvention-enabling technology, one must consider the effect that the anti-device provisions have on the research and development decisions of these manufacturers and, more generally, to patent law’s delicate incentive dynamic. Although the answer to this dilemma is beyond the scope of this Essay, this issue is something that scholars should pursue further.
Keywords: Copyright; Patents; Computers -- Access control; Digital Millennium Copyright Act of 1998; United States